PECULIARITIES OF INTERACTION BETWEEN LAW ENFORCEMENT AGENCIES IN SOLVING THE INVESTIGATION OF ILLICIT TRAFFICKING IN NARCOTIC DRUGS AND PSYCHOTROPIC SUBSTANCES - Kobilov Ulugbek Musurmonovich (Web of Journals Publishing, 2024)
The article analyzes the interaction of law enforcement agencies in uncovering the investigation of illicit trafficking in narcotic drugs and psychotropic substances and examines the features of tactical methods of interaction when conducting operational search activities and investigative actions.
Keywords: crime, illegal trafficking of narcotic drugs and psychotropic substances, law enforcement agencies, investigator, investigative actions, operational search activities.